Mozambique's industrialization - António Sousa Cruz; Dina Guambe; Constantino Pedro Marrengula; Amosse Francisco Ubisse (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
After the Second World War, Mozambique went through a series of transformations, from an incipient industrializing colonial society to an independent country with a central planned economy, plus a regional and internal war, and finally from 1994 onwards, a multi-party democracy with a mix of market economy and a still strong public hand. Although growing at more than 7 per cent annually since 1992, the economy is mostly based on low-productivity agriculture. Manufacturing contributes with less than 15 per cent of its GDP, but mineral coal and natural gas tend to expand significantly. The economy faces the challenge to diversify, integrate and industrialize.
Keywords: L1; L5; L6; O5; 330; manufacturing; investment; firms; policy; industrialization; Mozambique